2014
DOI: 10.1371/journal.pone.0090683
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Induces Pro-Inflammatory Cytokines and MMP Production via TLR4 in Nasal Polyp-Derived Fibroblast and Organ Culture

Abstract: Nasal polyposis is characterized by persistent inflammation and remodeling in sinonasal mucosa. Toll-like receptors (TLRs) play a role in the innate immune response to microbes in the sinonasal cavity. The aim of this study was to evaluate whether nasal polyp-derived fibroblasts (NPDFs) and organ-cultured nasal polyps can synthesize pro-inflammatory cytokines and matrix metalloproteinases (MMPs) after exposure to lipopolysaccharide (LPS), a TLR4 agonist. NPDFs and organ-cultured nasal polyps were isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 30 publications
(29 reference statements)
1
39
0
Order By: Relevance
“…HMGB1 mediated inflammatory signaling occurs through a number of potential receptors, including toll-like receptor (TLR)-4, [14][15][16][17] TLR-2, 15 and receptor for advanced glycation end products (RAGE). 18,19 Stimulation of these receptors has been shown to activate NF-kB pathway, which triggers the production of pro-inflammatory cytokines, such as IL-6 and MMP-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1 mediated inflammatory signaling occurs through a number of potential receptors, including toll-like receptor (TLR)-4, [14][15][16][17] TLR-2, 15 and receptor for advanced glycation end products (RAGE). 18,19 Stimulation of these receptors has been shown to activate NF-kB pathway, which triggers the production of pro-inflammatory cytokines, such as IL-6 and MMP-1.…”
mentioning
confidence: 99%
“…18,19 Stimulation of these receptors has been shown to activate NF-kB pathway, which triggers the production of pro-inflammatory cytokines, such as IL-6 and MMP-1. 4,13,16,20 In IVD, an elevated IL-6 level decreases expression of ECM constituents, aggrecan and Collagen Type II, 2,21 and is associated with the progression of DD 22 and with LBP associated with DD. 23 MMP-1 levels have also been shown to be elevated in lumbar DD patients.…”
mentioning
confidence: 99%
“…Viral infection causes impairment of macrophage phagocytic clearance (4) and epithelial barrier function (5,6), contributing to bacterial spread into the submucosa. Fibroblasts are the next cellular barrier beneath the respiratory epithelium and express the immune activation molecule CD40 (7), produce cytokines such as IL-6 and IL-8 in response to LPS (8), and respond to IFN-g by releasing T cell chemotactic CCL5 (9). Furthermore, studies focused on the skin (10) and synovial joints (11,12) indicate the potential for fibroblasts to activate Th cells directly through Ag presentation, however, this function in lung fibroblasts remains incompletely understood.…”
mentioning
confidence: 99%
“…LPS, the endotoxic part of the gram-negative bacteria, is often used to mimic inflammatory conditions in laboratory experiments. LPS combines with Toll-like receptor 4, which then activates the PI3K/Akt pathway [23,24], promoting the production of inflammatory cytokines and inducing unremitting inflammatory activity. In this study, our results showed higher levels of inflammatory cytokines, including TNF-α, IL-6, and IL-8, and nuclear proteins, such as NF-κB p65, when cells were incubated with LPS, indicating that inflammatory conditions were successfully created.…”
Section: Discussionmentioning
confidence: 99%